A case report of left ventricular thrombus formation following aggressive decongestion treatment. Issue 2 (14th February 2022) - Mystakidi, Vasiliki Chara; Oikonomou, Evangelos; Katsianos, Efstratios; Vavuranakis, Manolis
Abstract: Background: Intracardiac thrombi are a complication associated with cardiomyopathies. In heart failure with reduced ejection fraction, there is a hypercoagulable state that can increase the incidence of left ventricular thrombus and result in higher risk of thromboembolism, either manifested as stroke or as peripheral thromboembolic event. Haemoconcentration following decongestion treatment may enhance blood viscosity. Case summary: A 63-year-old man with known long-standing heart failure (HF) of ischaemic aetiology and not any prothrombotic risk, admitted with congestive HF and treated with aggressive decongestion treatment with intravenous loop diuretics. During his hospital stay, and following decongestion and haemoconcentration, a left ventricular (LV) intracardiac thrombus formation was detected by echocardiography, which occurred in the absence of a recent myocardial infarction or adverse LV remodelling. The patient was treated with oral anticoagulation therapy. There was a complete resolution of the thrombus on repeat transthoracic echocardiography after 4 weeks of treatment. Discussion: Aggressive decongestive treatment, haemoconcentration and increased blood viscosity following HF decompensation may serve as a trigger for intracardiac thrombus formation under the appropriate prothrombotic background. Appropriate primary antithrombotic prophylaxis is an issue raised concerns and vulnerable patients need closed clinical and imaging follow-up.